Collaborative Dynamics Of Stagist And Discursive Approaches In National Defense Policies Within Prismatic Societies - Toa, Akhmad Juni; Supranoto; Edy Wahyudi; M. Hamdi HS; Syamsul Maarif (Universitas Muhammadiyah Jember Press, 2023)
The national defense program in Situbondo Regency emphasizes collaboration between the Regional Leadership Coordination Forum (Forkopimda) of Situbondo and the Islamic boarding school (Pondok Pesantren) community in order to foster a participatory policy-making process. This collaboration is particularly crucial within a prismatic society, as it enables the integration of diverse forms of knowledge from each party within an inclusive public sphere. However, building such a partnership is not without challenges, as it involves navigating complex and sometimes conflicting interests between the two groups. This study aims to analyze the dynamics of collaborative national defense policy-making in Situbondo Regency, taking into account the prismatic nature of the local society. A qualitative approach was employed, using Interpretative Phenomenological Analysis (IPA) as the analytical method. The IPA approach was chosen to explore the collaborative processes involving both policy actors—namely, Forkopimda Situbondo—and target groups, particularly the ulama. The findings reveal that in the policy process, there is a clear divergence in the construction of knowledge between the policy actors and the target group. Forkopimda Situbondo tends to rely on professional and scientific (indigenous) knowledge, whereas the ulama draw more heavily on local (endogenous) knowledge. This divergence arises from differing policy approaches: Forkopimda adopts a stagist or managerial policy model, while the ulama engage through a discursive approach rooted in local ideas and narratives. Despite these differences in approach and epistemological orientation, the two groups have managed to establish effective collaboration. This is evident in several joint activities, such as the celebration of Indonesia’s Independence Day and the commemoration of the 74th National Defense Day (HBN).